Digital technologies, equitable gender norms, and sexual health practices across sexting patterns among forcibly displaced adolescents in the slums of Kampala, Uganda. (January 2023) - Okumu, Moses; Logie, Carmen H.; Ansong, David; Mwima, Simon; Hakiza, Robert; Newman, Peter A.
Abstract: Sexting is increasing among adolescents globally and may be an indicator of sexual activity. Yet researchers know little about sexting patterns of forcibly displaced urban adolescents. We sought to identify patterns of sexting among these adolescents and to determine how sexting patterns differed by adolescents' digital technology use, support of equitable gender norms, and sexual health practices. Using data from a community-based sample, we identified three groups: non-sexters, or individuals who did not sext ( n = 205; 84.7%); moderate sexters, or individuals who received sexually explicit texts and nude pictures, but only sent texts ( n = 13; 5.4%); and poly-sexters, or individuals who sent and received both texts and nude pictures ( n = 24; 9.9%). We observed differences between sexting patterns and digital technology use, gender norms, and sexual health practices. Understanding these sexting patterns may inform the development and implementation of digital sexual health interventions for forcibly displaced adolescents. This study highlights potential positive outcomes associated with sexting (i.e., condom efficacy and use) as well as its concerning correlated factors (e.g., less access to sexual and reproductive health services) among refugee adolescents. Based on these findings, we offer recommendations for future digital sexual health interventions. Highlights: There were 3 groups of sexters. Non sexters were the most prevalent type of sexter (84.7%). Moderate sexters were mostly adolescent girls, digital technology users, and had high equitable gender norms. Poly sexters were mostly adolescent boys who reported high condom efficacy and use.